Influence of Base Oil on Planar Double Enveloping Hourglass Worm Drive - Fayang He; Zhanshan Li (Jixie chuandong)
In order to study the influence of different base oils on the lubrication of planar double enveloping hourglass worm drive，running in test is carried out. It is found that，when using polyethylene glycol synthetic oil，the transmission efficiency increases by 4.5% and the temperature rise is 15 ℃ lower than that of poly-alpha-olefins synthetic oil. When mineral oil is used，the transmission efficiency will be reduced by about 10%，and the temperature rise will increase by more than 58 ℃. Polyethylene glycol synthetic oil has the better performance for long-term continuous working plane double enveloping hourglass worm reducer. Mineral oil is only suitable for discontinuous operation and low load applications. When heat dissipation measures are taken，poly-alpha-olefins synthetic oil can be used. Further research shows that the minimum film thickness is not enough to fully reflect the difference of transmission efficiency and temperature rise caused by different base oils，but it can be used to evaluate the lubrication state.